التغيرات المناخية وتأثيراتها على صحة الانسان في العراق - صاحب طالب الموسوي, أ.د علي (Journal of College of Education, 2021)
Chemical changes are considered as one of the most important environmental problems because their danger affected the humanity and they became are clear all over our earth . The latest report issued by the United Nations showed these effects and studied in (Bali) Conference in Indonesia nearly at the end of 2007 which assured that all the proofs about the climate changes in the earth are of no doubt . The idea of the climate changes is defined as a disorder in the usual climatic circumstances of the climatic elements which differentiate any region from the other . When talking about the changing of the climate of the earth , it means the changes of the climate of the earth climate in general . The climatic changes lead to great effects on the natural active systems . There is a different between the climate change and the climate fluctuation . The climate change is defined as a disorder in the usual climatic circumstances of the climate elements which differentiate each region from the other . While the climate fluctuation means happening great changes with any element of the climate elements and they differ from the general average . The climatic periodicities means the difference from the general average of the values of any element of the climate . A number of the geologists studied the climatic changes through the geological ages by the proofs of the deposit rocks . Some scientists think that there are two reasons of the climatic changes of the earth which cause dramatic geological and biological changes . One of those reasons is the change of the location of the continents which has local effects on limited area of the earth . Therefore they are known as (local climate changes) . While the other reasons have universal changes . Most scientific studies agree that the reasons of the climatic changes are natural reasons produced by internal operations happening inside the components of a climate system which affects them and affected by them and human reasons as a result of the various human activities .